Prevalence and predictors of under-nutrition among school children in a rural South-eastern Nigerian community: a cross sectional study - Rufina N. B. Ayogu; Ifeoma C. Afiaenyi; Edith U. Madukwe; Elizabeth A. Udenta (BMC, 2018)
Abstract Background School children in developing countries like Nigeria are faced with numerous nutrition and health problems. Lack of functional school health and nutrition programmes in Enugu state, Nigeria may be associated with dearth of data on associated factors. Identifying these factors could inform the design and implementation of school-based programmes aimed at ameliorating these problems. Methods A cross sectional survey involving 450 primary and secondary school children aged 6-15 years was conducted in Ede-Oballa, a rural community in Enugu state, South-eastern Nigeria. Selection of the pupils was by multistage sampling technique. Data were collected through interviewer administered questionnaire, anthropometric measurements of weight and height, 3-day weighed food intake, stool microscopy and blood analyses for malaria, zinc and vitamin A. Bivariate and multivariate logistic regression analyses were used to evaluate associations of interest with significance accepted at P < 0.05. Results The school children were affected by underweight (18.2%), stunting (41.6%), thinness (20.0%), zinc (43.3%) and vitamin A (51.1%) deficiencies. After adjusting for potential confounders, weekly food expenditure was a major predictor of under-weight (AOR = 0.19, 95% CI: 0.08, 0.46), stunting (AOR = 0.36, 95% CI: 0.13, 0.95) and thinness (AOR = 0.49, 95% CI: 0.30, 0.80); household income was also a predictor of thinness (AOR = 0.47, 95% CI: 0.25, 0.88). Males had lower odds of being stunted than females (AOR = 0.31, 95% CI: 0.11, 0.83). The odd of being underweight was higher in female headed households than in households headed by males (AOR = 0.30, 95% CI: 0.12, 0.75). Tapeworm was an independent predictor of vitamin A (AOR = 3.59; 95% CI: 1.06, 12.13) and zinc (AOR = 3.64; 95% CI: 1.02, 12.98) deficiencies. Children with whipworm were more likely to be zinc (AOR = 3.80; 95% CI: 1.11, 13.04) and vitamin A (AOR = 3.79; 95% CI: 1.12, 12.89) deficient than those uninfected. Conclusion Underweight, stunting, thinness, vitamin A and zinc deficiency among the school children were functions of weekly food expenditure, gender of household head and household income, tapeworm, whipworm, and sex. These findings emphasize the need for effective school- and community-based interventions.